ANALISIS EVALUASI MEDIA PEMBELAJARAN - Ayu Nur Chamidah; Hamam Burhanuddin (Lembaga Penelitian, Penerbitan dan Pengabdian kepada Masyarakat (LP3M) IAIFA Kediri, 2026)
The evaluation of instructional media is a systematic process conducted to assess the effectiveness, quality, and feasibility of media used in the learning process. This study employs a literature review method by gathering information from books, journals, and digital references related to instructional media evaluation. The findings indicate that evaluation is essential to ensure that media supports learning objectives, facilitates students’ understanding, and enhances motivation and engagement. Evaluation can be carried out through formative and summative approaches, supported by logical and empirical analysis of assessment instruments. Furthermore, evaluation criteria include content quality, instructional quality, and technical quality, which serve as the main indicators for determining the value of the media. Overall, instructional media evaluation plays a crucial role in improving the quality of learning and helps teachers develop more effective and innovative learning strategies that align with technological advancements in education